2017
DOI: 10.1097/ccm.0000000000002377
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Second Dose Antibiotics for Patients Admitted From the Emergency Department With Sepsis: Prevalence, Risk Factors, and Outcomes*

Abstract: Major second dose delays were common, especially for patients given shorter half-life pharmacotherapies and who boarded in the emergency department. They were paradoxically more frequent for patients receiving compliant initial care. We observed association between major second dose delay and increased mortality, length of stay, and mechanical ventilation requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
3
31
1
1
Order By: Relevance
“…The importance of timing and appropriateness of the first dose of antibiotics has been shown in previous studies, especially in septic shock [9][10][11][12][13][14][15]33]. Leisman et al studied the importance of timely administration of the 2nd dose and showed that major delay in the 2nd dose was associated with higher mortality [17]. Therapeutic antibiotic concentrations in blood and at the target site must be achieved and maintained as quickly as possible in order to reduce bacterial load [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of timing and appropriateness of the first dose of antibiotics has been shown in previous studies, especially in septic shock [9][10][11][12][13][14][15]33]. Leisman et al studied the importance of timely administration of the 2nd dose and showed that major delay in the 2nd dose was associated with higher mortality [17]. Therapeutic antibiotic concentrations in blood and at the target site must be achieved and maintained as quickly as possible in order to reduce bacterial load [20].…”
Section: Discussionmentioning
confidence: 99%
“…The timing of the 2nd dose of an appropriate antibiotic with renal elimination took into consideration the increased dose interval due to reduced renal excretion. When more than one adequate antibiotic was given, the longest recommended dose interval was applied [17]. The ratio for time interval between the first and second doses was calculated as the actual time divided by the recommended time interval.…”
Section: Definitions Of Appropriate and Early Antibiotic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical period between ED‐ and inpatient‐based care also provides opportunities for quality improvement, with a recent observational study finding delays to second doses of antibiotic in sepsis were common (delay of ≥25% dosing interval in one‐third of cases). This delay was associated with increased mortality, length of stay and requirement for mechanical ventilation . Routine prescription of weight‐based initial antibiotic doses for appropriate drugs as well as subsequent regular doses should be encouraged in the ED.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Недавнее исследование [75] показало, что среди па циентов с сепсисом, находящихся в отделении неотлож ной помощи, более чем у 50% пациентов имела место задержка введения первой и второй дозы антибиотика, равная примерно 4 ч. (для 6часовых интервалов до зирования).…”
Section: клинические рекомендацииunclassified